1990
DOI: 10.1530/jrf.0.0890205
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-specific protein B and progesterone concentrations in French Alpine goats throughout gestation

Abstract: Summary. The 34 French Alpine dairy goats originated from a single flock and were artificially inseminated 44 h after synchronization of oestrus. They were bled daily at the jugular vein from 15 to 27 days after AI. An early pregnancy diagnosis by RIA of progesterone concentration was performed 21 days after AI. In pregnant goats (\ m=ge\1\ m=. \ 5ng progesterone/ml) daily sampling was extended until 30 days after AI and, from those, 9 were bled every 2 weeks until the end of pregnancy and at 50 and 63 days po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
1
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 23 publications
2
26
1
3
Order By: Relevance
“…Moreover, heterologous PAG tests were also useful for pregnancy diagnoses in wild ruminants, i.e. wood bison [107], moose [108], rocky mountain elk [109], white-tailed deer [110,111], mule deer [111], red deer [112], sika deer [113], fallow deer [114,115], mountain goat [116] and Alpine goats [117][118][119]. The measurement of PAG protein concentrations in maternal blood or milk of ruminants allow for 76.6-100% accuracy rates for early pregnancy diagnoses [120,121] and provide an alternative method to ultrasonography for determining late embryonic mortality [96,122].…”
Section: Pregnancy Diagnostic Pag Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, heterologous PAG tests were also useful for pregnancy diagnoses in wild ruminants, i.e. wood bison [107], moose [108], rocky mountain elk [109], white-tailed deer [110,111], mule deer [111], red deer [112], sika deer [113], fallow deer [114,115], mountain goat [116] and Alpine goats [117][118][119]. The measurement of PAG protein concentrations in maternal blood or milk of ruminants allow for 76.6-100% accuracy rates for early pregnancy diagnoses [120,121] and provide an alternative method to ultrasonography for determining late embryonic mortality [96,122].…”
Section: Pregnancy Diagnostic Pag Testsmentioning
confidence: 99%
“…In cattle and goats, the PAG concentration increases as pregnancy progresses [80,97,119]. In sheep, the concentration pattern of the PAGs is biphasic [99,102,104], increases (300−400 ng.mL −1 ) during the second month of pregnancy, when chorionic cells have intensively proliferated and the placenta was formed.…”
Section: Pregnancy Diagnostic Pag Testsmentioning
confidence: 99%
“…In goats, placenta does not produce sufficient amount of progesterone, and therefore goats are fully dependent on luteal progesterone for maintenance of pregnancy. As in most animals, plasma progesterone concentration in goats is high during the gestation period and decreases abruptly before parturition [2][3][4][5][6]. In addition, increased levels of 20α-OHP have also been observed in the general circulation during pregnancy in goats [2].…”
mentioning
confidence: 98%
“…Development of specific RIA and EIA for the presence of pregnancy associated proteins of feto-placental origin in the maternal serum 3-4 wks after conception has been used as a serological marker for pregnancy diagnosis in cattle [53], sheep and goats [54]. During gestation of cow, the concentrations of PAG are detectable as early as from the 19 th to 22 nd days after the conception, to reach concentrations from 3 to 6 ng/ml in the neighborhoods of the 33 rd to 37 th days of gestation [55,56] reported that PAG concentrations increased continuously from day 20 of pregnancy until day 240 followed by a dramatic increase in the last ten days of pregnancy with maximum concentrations between day 5 and day 1 prepartum.…”
Section: Pregnancy Associated Glycoprotein (Pag)mentioning
confidence: 99%
“…Between the 9 th and the 19 th week the level remained constant, thereafter a drastic surge occurs, reaching a peak at parturition. Recently Rovani et al [54] detected pregnancy accurately using bovine ELISA kit in sheep 33 days following mating, while PAGs levels from the previous gestation are no longer detected from 21 days postpartum. The accuracy of the ELISA test was 96.1% from 33 days of pregnancy until lambing.…”
Section: Pregnancy Associated Glycoprotein (Pag)mentioning
confidence: 99%